Intestinal paracellular permeability during malnutrition in guinea pigs: effect of high dietary zinc. Issue 3 (September 1996) - Rodriguez, P; Darmon, N; Chappuis, P; Candalh, C; Blaton, M A; Bouchaud, C; Heyman, M
Abstract : BACKGROUND: Zinc has been shown to have beneficial effects in vitro on epithelial barrier function, and in vivo to reduce intestinal permeability in malnourished children with diarrhoea. AIMS: To determine whether malnutrition alters intestinal paracellular permeability, and whether zinc prevents such alterations. METHODS: Guinea pigs were fed a normal protein diet (NP group), a low protein diet (LP group), or a low protein diet enriched with 1800 ppm zinc (LPZn group) for three weeks. Intestinal permeability was measured on jejunal segments mounted in Ussing chambers by measuring ionic conductance and mucosal to serosal fluxes of 14C-mannitol, 22Na, and horseradish peroxidase. Tight junction morphology was assessed on cryofracture replicas. RESULTS: Mannitol and Na fluxes and ionic conductance increased in the LP group compared with the NP group but remained normal in the LPZn group. Accordingly, jejunal epithelia from the LP group, but not from the LPZn group, showed a small decrease in number of tight junctional strands compared with epithelia from the NP group. Neither malnutrition nor zinc treatment modified horseradish peroxidase fluxes. CONCLUSIONS: Malnutrition is associated with increased intestinal paracellular permeability to small molecules, and pharmacological doses of zinc prevent such functional abnormality.